(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and profound disturbances in carbohydrate, lipid, and protein metabolism. Experimental models of diabetes have been widely used to investigate the pathophysiological mechanisms underlying diabetic complications, particularly those involving the microvasculature. Among these models, alloxan-induced diabetes remains one of the most established and reproducible experimental approaches for studying insulin-deficient diabetes and its systemic consequences. Alloxan selectively destroys pancreatic β-cells through oxidative stress mechanisms, leading to rapid onset of hyperglycemia and metabolic dysregulation that closely mimic key aspects of human diabetes.